Design Engineering, Volumes 1 and 2 2003
DOI: 10.1115/imece2003-42415
|View full text |Cite
|
Sign up to set email alerts
|

Assembly Quality Methodology: A New Method for Evaluating Assembly Complexity in Globally Distributed Manufacturing

Abstract: As suggested by several past studies (Barkan and Hinckley, 1993; Eking, 1988; Gebala, 1992; Beiter et al., 2000; Shibata et al., 2001), complexity in the assembly process has a strong correlation with the occurrence of defects. The authors propose a new method that uses a product’s complexity to predict defect rate (Shibata et al., 2001 and 2003). This method provides metrics for assembly complexity using two engineering measures: 1) assembly time estimates and 2) ease-of-assembly ratings. Extensive field data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 0 publications
0
63
0
Order By: Relevance
“…Moreover, this approach requires actual production data such as: number of defects occurred over a period of time, and does not consider assembly design complexity factor. Hence, [37] modified Hinckley's approach by combining process and design based complexity factors, where these factors are represented as a function of number of job elements in the assembly workstation, an arbitrarily selected assembly time, and completion time of individual tasks based on the method of Sony Standard Time (SST). In Shibata's method, design complexity factor is defined as the ratio between a subjectively selected calibration coefficient and ease of assembly coefficient of the corresponding workstation estimated by means of assembly/disassembly cost-effectiveness (DAC) method.…”
Section: Common Practices On Measuring Product Assembly Complexitymentioning
confidence: 99%
“…Moreover, this approach requires actual production data such as: number of defects occurred over a period of time, and does not consider assembly design complexity factor. Hence, [37] modified Hinckley's approach by combining process and design based complexity factors, where these factors are represented as a function of number of job elements in the assembly workstation, an arbitrarily selected assembly time, and completion time of individual tasks based on the method of Sony Standard Time (SST). In Shibata's method, design complexity factor is defined as the ratio between a subjectively selected calibration coefficient and ease of assembly coefficient of the corresponding workstation estimated by means of assembly/disassembly cost-effectiveness (DAC) method.…”
Section: Common Practices On Measuring Product Assembly Complexitymentioning
confidence: 99%
“…At the beginning of the 2000s, Shibata [41] reported that on average, 42% of the assembly defects in products such as compact disc/mini disc dual-deck players were due to human error. This work also revealed that assembly process complexity increases the human error rate and hence the occurrence of defects.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [43] later showed the direct relationship between human error and economic loss in production and developed a loss estimation model in which the impact of human error is categorized as minor, medium, or severe. Considering 33 types of cost factor, the effect of complexity on quality in consumer audio equipment assembly has been analyzed at various sites around the world using a vast field dataset [41]. In the recent literature, researchers now recommend integrating production and human factors [44] as well as maintenance [45] and human error probability (HEP) to improve production system reliability [46].…”
Section: Discussionmentioning
confidence: 99%
“…model "think time" (when making choices), job complexity, and operator's experience. Hinckley (1993) and Shibata (2002) present models to predict defects based on the number of assembly operations in the semiconductor industry. Su et al (2010) apply a similar concept to predict defects in copier manufacturing.…”
Section: Production Complexity and Entropymentioning
confidence: 99%